Progenitor and stem cells for bone and cartilage regeneration - El Tamer, M. K. (2009)
Research in regenerative medicine is developing at a significantly quick pace. Cell-based bone and cartilage replacement is an evolving therapy aiming at the treatment of patients who suffer from limb amputation, damaged tissues and various bone and cartilage-related disorders. Stem cells are undifferentiated cells with the capability to regenerate into one or more committed cell lineages. Stem cells isolated from multiple sources have been finding widespread use to advance the field of tissue repair. The present review gives a comprehensive overview of the developments in stem cells originating from different tissues and suggests future prospects for functional bone and cartilage tissue regeneration.